Simultaneous Proximinality in Spaces of Bochner Integrable Functions. (18th August 2018) - Rao, T. S. S. R. K.
Abstract: We study closed sets of spaces of Bochner integrable functions that are simultaneously proximinal. We show that the set of weakly compact convex set-valued Bochner integrable functions is a simultaneously proximinal set in the corresponding Banach space of functions.